The Moderation Role of Government Policy on the Effect of Intellectual Capital on the Performance of Small and Medium Enterprise: Peran Moderasi Kebijakan Pemerintah Terhadap Pengaruh Intellectual Capital Terhadap Kinerja Usaha Kecil Menengah - Indira, Irma; Kartikasari, Evi Dwi; Sulton, Muhammad; Priyatna, Deddy; Prasetyo , Haris (Universitas Muhammadiyah Sidoarjo, 2023)
The objective of this study is to test 1)whether the performance of SMEs in Kramat Mengare Village can be influenced by human capital, 2) the influence of technology capital on the performance of SMEs in Kramat Mengare Village, 3) government policies that moderate the influence of human capital on the performance of SMEs, and 4) government policies that moderate the influence of technology capital on the performance of SMEs. In this study, the sample was 200 respondents from SMEs in Kramat Mengare Village, and the data collected using purposive sampling was used in this study. The measurement used the Likert scale to obtain primary data in this study. The analytical method used in this study uses Structural Equations Modeling with PLS 3.2.7. The study's validity and reliability test results show that the data obtained are valid and reliable. Hypothesis testing in PLS 3.2.7 shows the results that SMEs of Mengare Village can be influenced by human capital and technological capital and the performance of SMEs Kramat Mengare Village cannot be influenced by human capital and technological capital which is moderated by government policy. This research has implications especially for SMEs in the village who are aware of the importance of technology for business development and are aware of their ability to quality products and the importance of government policies in supporting SMEs